2019
DOI: 10.1038/s41598-019-49696-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Surfactant Protein B Deficiency in Patient Specific Human Induced Pluripotent Stem Cell Derived Lung Organoids by Gene Therapy

Abstract: Surfactant protein B (SFTPB) deficiency is a fatal disease affecting newborn infants. Surfactant is produced by alveolar type II cells which can be differentiated in vitro from patient specific induced pluripotent stem cell (iPSC)-derived lung organoids. Here we show the differentiation of patient specific iPSCs derived from a patient with SFTPB deficiency into lung organoids with mesenchymal and epithelial cell populations from both the proximal and distal portions of the human lung. We alter the deficiency b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 64 publications
1
71
0
Order By: Relevance
“…As discussed in some of the examples above, iPSC-derived epithelial, immune cell, and organoid models can be used as a powerful screening tool for precision therapy ( Table 1). ALI cultures and organoids derived from primary cells or iPSC maintain the patient's genetic, functional and phenotypic signatures in vitro, allowing for accurate prediction of drug responses of individual patients (Gras et al, 2012;Bartfeld and Clevers, 2017;Oost et al, 2018;Kim et al, 2019;Leibel et al, 2019). In combination with genetic modification tools, such as lentiviruses or CRISPR/Cas9, organoids, and ALI cultures can be used to study the effects of specific genetic mutations in various diseases and identify potential drug targets and cell therapies (Schwank et al, 2013;Zhou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in some of the examples above, iPSC-derived epithelial, immune cell, and organoid models can be used as a powerful screening tool for precision therapy ( Table 1). ALI cultures and organoids derived from primary cells or iPSC maintain the patient's genetic, functional and phenotypic signatures in vitro, allowing for accurate prediction of drug responses of individual patients (Gras et al, 2012;Bartfeld and Clevers, 2017;Oost et al, 2018;Kim et al, 2019;Leibel et al, 2019). In combination with genetic modification tools, such as lentiviruses or CRISPR/Cas9, organoids, and ALI cultures can be used to study the effects of specific genetic mutations in various diseases and identify potential drug targets and cell therapies (Schwank et al, 2013;Zhou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, transcriptomic analyses of these organoids treated with two drugs known to impact on AEC2 cells, namely amiodarone and GNE7915, provided putative mechanistic insights as to how these two drugs differentially induce toxicity (Yamamoto et al, 2017). In addition, several reports have shown that organoids derived from primary HBEC or patient specific iPSC maintain the patient's genetic and phenotypic signatures in vitro (Gras et al, 2012;Kim et al, 2019;Leibel et al, 2019). Thus overall, the spherical culture is a promising tool to study lung development and can be used to model a variety of chronic and infectious diseases.…”
Section: Lung Organoidsmentioning
confidence: 99%
“…To circumvent this limitation, several groups have developed methods to differentiate hPSCs into progenitors of the lung epithelium, [ 33 , 34 , 36 , 52 , 63 , 66 ] which can then give rise to alveolar cell types, partially recapitulating the development of the lung epithelium during sacculation and alveologenesis. Methods also exist to generate more purified populations of alveolar cells called alveolospheres, [ 22 , 34 , 101 , 102 , 130 ] which have already proven useful for modeling congenital disease of the alveoli [ 131 , 132 ] and alveolar injury. [ 133 ] These methods, although state-of-the-art, provide an incomplete picture of sacculation and alveolar development in humans because they either lack mesenchyme, [ 63 , 66 , 101 ] require exogenous mesenchyme for alveolar differentiation, [ 34 , 102 ] generate immature alveolar cells stochastically, [ 33 , 36 , 52 , 63 , 66 ] or give rise to ATII cells only.…”
Section: Saccular and Alveolar Stages Of Respiratory Developmentmentioning
confidence: 99%
“…They also offer the opportunity to correct genetic defects prior to transplantation in mutation‐carrying patients. Using lentiviral and CRISPR‐Cas9 technologies, iPSCs isolated from patients suffering from a variety of diseases affecting various organs, including Duchenne muscular dystrophy (Hagan, Ashraf, Kim, Weintraub, & Tang, ), surfactant protein B deficiency (Jacob et al, ; Leibel et al, ), and ciliopathic renal disorder (Forbes et al, ), have been successfully corrected in vitro . Knowledge gained from ESC studies has allowed for rapid advances in the utilization of iPSCs for regenerative purposes (Ghaedi et al, ).…”
Section: Recellularization Of Acellular Scaffoldsmentioning
confidence: 99%